2021
DOI: 10.1113/jp281002
|View full text |Cite
|
Sign up to set email alerts
|

An MRI approach to assess placental function in healthy humans and sheep

Abstract: Key points Human placental function is evaluated using non‐invasive Doppler ultrasound of umbilical and uterine artery pulsatility indices as measures of resistance in placental vascular beds, while measurement of placental oxygen consumption (VnormalO2) is only possible during Caesarean delivery. This study shows the feasibility of using magnetic resonance imaging (MRI) in utero to measure blood flow and oxygen content in uterine and umbilical vessels to calculate oxygen delivery to and VnormalO2 by the grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 122 publications
0
37
0
Order By: Relevance
“… 108 In recent years, several magnetic resonance imaging approaches for the assessment of placental function and fetal cardiovascular physiology in sheep have also been developed. 109 These noninvasive techniques provide indispensable approaches to identifying placental and fetal cardiometabolic dysfunction in complicated pregnancy. Such technologies hold significant promise which will help in the translation of potential interventions, such as the use of mitochondria-targeted antioxidants, into the human clinical situation.…”
Section: Hypoxia: Long-term Effects On the Fetusmentioning
confidence: 99%
“… 108 In recent years, several magnetic resonance imaging approaches for the assessment of placental function and fetal cardiovascular physiology in sheep have also been developed. 109 These noninvasive techniques provide indispensable approaches to identifying placental and fetal cardiometabolic dysfunction in complicated pregnancy. Such technologies hold significant promise which will help in the translation of potential interventions, such as the use of mitochondria-targeted antioxidants, into the human clinical situation.…”
Section: Hypoxia: Long-term Effects On the Fetusmentioning
confidence: 99%
“…Placental pathology may provide input into a stroke risk stratification algorithm, but the timeframe required for placental examination will be a limiting factor until new techniques are developed that can offer real-time, clinically-relevant information. In order to establish preventative strategies, advanced methods of in utero assessment are needed, such as the many emerging methods in advanced placental magnetic resonance imaging ( 43 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the limitations in assessing human placental function non‐invasively, recent studies have demonstrated the feasibility of using MRI to measure blood flow and oxygen content in the uterine and umbilical vessels to calculate oxygen delivery and uteroplacental oxygen consumption (Saini et al . 2020, 2021). While these innovative techniques may be able to better quantify the impact of maternal positioning on fetal wellbeing, the difficulty lies in applying these techniques to a maternal sleep state where cardiovascular and respiratory function is altered.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of the CTG in an antenatal setting can be challenging, but the pathophysiological adaptations and responses of the fetus seen intrapartum can be extrapolated to the antenatal setting to provide a real-time assessment of fetal wellbeing to hypoxic challenges (Judd et al 2020). Given the limitations in assessing human placental function non-invasively, recent studies have demonstrated the feasibility of using MRI to measure blood flow and oxygen content in the uterine and umbilical vessels to calculate oxygen delivery and uteroplacental oxygen consumption (Saini et al 2020(Saini et al , 2021. While these innovative techniques may be able to better quantify the impact of maternal positioning on fetal wellbeing, the difficulty lies in applying these techniques to a maternal sleep state where cardiovascular and respiratory function is altered.…”
Section: Strengths and Limitationsmentioning
confidence: 99%